Archive Management Analysis in Secondary School: A Case Study in Indonesia - Suharti Suharti; Haedar Akib; Jamaluddin Jamaluddin; Kassim Thukiman (Har Press Indonesia, 2020)
Archiving is all activities relating to the management of archives, both official and private archive. This study aims to determine the implementation of records management at secondary school. In this study, there are five indicators, namely, receipt of the archive, archival storage, maintenance and security of the archive, as well as depreciation of the archive, and destruction of records. The research method applied in this study is descriptive qualitative. Data collection techniques used are observation, interview, and documentation. Five informants participated in this study. Analysis of the data used is an interactive model and the techniques in analyzing data are by performing data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, an extension of observation was carried out for triangulation of data sources, holding member checks, and increasing diligence in conducting the study. The results of this study indicate that the implementation of records management in secondary school is still very simple and not in accordance with the development of existing archival science. Judging from the lack of facilities and infrastructure management records that are needed and the absence of an archive management system used to organize the archive. Thus, to find back an archive still takes a long time and sometimes even have to do records archiving. So, in this case, the management of the archive is considered less than the maximum and ineffective